Necesidad de incorporar en la ley de comercio electronico, firmas electronicas y mensajes de datos, la informatica juridica como herramienta que permita agilitar y optimizar las actividades judiciales, administrativas, y notariales - Palomo Guamani, Manuel Roberto (2015)
This legal research falls within the academic problems of Information Law, in particular the Law on Electronic Commerce, Electronic Signatures and Data Messages Ecuadorian research that meets the requirements established by the Regulations of the University Academic System Nacional de Loja, which regulates the relevance of the research study legal aspects inherent in the materials of positive law, to opt for the law degree from the Courts of the Republic of Ecuador. This research aims to demonstrate that the Law on Electronic Commerce, Electronic Signature and Data Messages, suffers from legal failure by not co0ntener in its regulations as related to Legal Informatics technological instrument of singular importance in the era of advanced technological development. The subject of this research deals with different aspects of what constitutes legal information in the conceptual, doctrinal, legal field, in the field of comparative law, in the analysis of the criteria given in surveys and interviews. So in the conceptual aspect, a conceptual analysis of what constitutes the legal Computing, its characteristic features, computer classes and Legal Management, Legal Informatics Documentary, Documentary Language, Electronic Signature, Digital Signature, Electronic Records, Electronic Signatures is performed, Data Messages. Within the legal framework analysis what about the Computer and technological instruments indicated by the Constitution of the Republic takes place in the Art. 16, which speaks of the Right to Communication, Art, 18 of the Right to Information, Art . 25 Scientific Progress and ancestral knowledge, Analysis of the Law on Electronic Commerce, Electronic Signatures and Data Messages, the Communications Law, the Organic Code of Judicial Function of Comparative Law. In the doctrinal aspect views and opinions about what constitutes Computers, the historical evolution of Information Law, its implementation in the administrative, judicial field and information are reviewed. Finally, the issue of field research formulation comprising surveys, interviews, analysis of results, drawing conclusions, recommendations and proposed legal reforms addressed. The use of the Internet, in the process of globalization we are living, is creating a revolution in the way business, trade and computer law are handled in regard to the judiciary in our country is ready professional and technologically to meet its obligation to deliver justice. Every time creating appropriate legislation to enable greater participation of people in the world of electronics, public administration, the judiciary is necessary.